Pronunciation Quality as an Important Factor of Language Competence - Żytyńska, Małgorzata (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
This article contains reflections on the relevance of pronunciation quality for language competence, as well as on the use of pronunciation exercises within the respective vocational education and training. On the one hand, the quality of pronunciation seems to be underestimated more and more, but on the other hand, there are many professions, where correct and clear pronunciation proves to be conditio sine qua non, be it in the mother tongue or in the foreign language. Because little time and attention is devoted to this aspect within education, external courses on voice formation and pronunciation workshops are becoming more and more popular. That is why the postulate is pressing here, that the pronunciation should be generously included in the university education of many disciplines.